THE EFFECT OF PROFITABILITY, LIQUIDITY, GROWTH SALES, OPERATING LEVERAGE AND TANGIBILITY ON CAPITAL STRUCTURE (evidence from manufacture firm listed on Indonesia stock exchange in 2011- 2014) - Hamidah, Hamidah; Iswara, Diana; Mardiyati, Umi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
The purpose of this study is to know the effect of profitability, liquidity, sales growth, operating leverage and tangibility on capital structure: evidence from manufacture firm listed on Indonesia Stock Exchange in 2011-2014. The sample using in this study is 41 companies. The research model in this study employs panel data analysis (unbalanced panel) with fixed effect approach. The result show that profitability and liquidity have negative and significant effect on capital structure. Sales growth and operating leverage have positive but not significant effect on capital structure. Tangibility have negative and not significant effect on capital structure. Key words: Profitability, liquidity, sales growth, operating leverage, tangibility, capital structure, manufacture firm